2019
DOI: 10.3389/feduc.2019.00092
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Satisfaction in Webinar, Online, and Face-to-Face Instruction: A Meta-Analysis

Abstract: Kirkpatrick's four-level training evaluation model assumes that a positive correlation exists between satisfaction and learning. Several studies have investigated levels of satisfaction and learning in synchronous online courses, asynchronous online learning management systems, and synchronous face-to-face classroom instruction. The goal of the present meta-analysis was to cumulate these effect sizes and test the predictive validity of Kirkpatrick's assumption. In this connection, particular attention was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 44 publications
9
100
2
6
Order By: Relevance
“…Interestingly, our study found that the higher the self-reported academic performance, the lower the evaluation of the ongoing online education. This finding is in line with the study by Ebner and Gegenfurtner, 7 which showed a negative association between learning performance and satisfaction with online courses. This may be because it is difficult for online courses to meet all of students’ personalised learning needs, 13 especially those who have high self-evaluations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, our study found that the higher the self-reported academic performance, the lower the evaluation of the ongoing online education. This finding is in line with the study by Ebner and Gegenfurtner, 7 which showed a negative association between learning performance and satisfaction with online courses. This may be because it is difficult for online courses to meet all of students’ personalised learning needs, 13 especially those who have high self-evaluations.…”
Section: Discussionsupporting
confidence: 92%
“… 15 Moreover, academic performance has been found to have a negative impact on students’ evaluations of online courses, that is, students with a higher academic performance tend to yield a low level of evaluations. 7 Therefore, there is a need to pay more attention to students’ perceptions of online learning to explore more details about the effectiveness of online education from the subjective view of students.…”
Section: Introductionmentioning
confidence: 99%
“…Harned et al , ; Kanter et al , ; Wang & Hsu, ). Still, even if trainees were satisfied with the evaluated webinars, we should note that Ebner and Gegenfurtner () reported trainees to be even more satisfied in face‐to‐face instruction compared with webinar instruction.…”
Section: Discussionmentioning
confidence: 80%
“…The value and acceptability of webinar platforms to deliver training to groups is well-documented, often with good learning outcomes. (37)(38)(39)(40)(41)(42)(43) As the technology and tools that facilitate delivery of training through this evolving medium continue to mature, those seeking to raise awareness of emerging health threats such as Chagas disease recognize the invaluable worth of embracing this technology and assessment of learning. (44) The results of the pre-and post-test evaluations in this study indicate an increase in overall knowledge of Chagas disease among the healthcare professionals who participated in the webinar.…”
Section: Discussionmentioning
confidence: 99%